Dietary habits and obesity among adolescent school children: A case control study in an urban area of kancheepuram district - G Angeline Grace; Shanthi Edward; S Gopalakrishnan (Wolters Kluwer Medknow Publications, 2021)
Background: Obesity is an important public health problem and is on the rise among adolescents in developed and developing nations. This case-control study was done to assess the dietary risk factors associated with obesity among school children of the adolescent age group. Materials and Methods: This study was done among age-matched 110 cases and 110 controls who were adolescent children between ages 10 and 17 years. Data were collected using a pretested, structured, interviewer-administered questionnaire and was analyzed using descriptive and analytical statistics. Results: About 52.7% of children belonged to the age group 13-15 years. Adequate fruits intake was reported by 42.7% of obese adolescents and 60% of nonobese adolescents. Adequate intake of vegetables was noted in 20.9% of cases and 24.5% of controls. The risk factors which were found to be statistically associated with adolescent obesity were increased fast food intake, sweets consumption, inadequate fruit intake, and the liberty given by the parents in purchasing snacks. Conclusions: Since adolescent obesity is rising at an alarming rate, the dietary determinants of obesity need to be addressed at the level of schools, families, and community. School health services should include education on healthy food habits and regular monitoring of the health status of children. Parents need to be aware on the significance of balanced diet, avoidance of junk foods, and ensure adequate intake of fruits and vegetables for their children to prevent early onset of noncommunicable diseases.